PENINGKATAN HASIL BELAJAR MENGGUNAKAN PROJECT BASED LEARNING BERBANTUAN MATHIGON PADA MATERI BANGUN RUANG KELAS V SDN 33 SAWAHAN KOTA PADANG - Almadani, Wahyuda; Engreini, Syofianti; Suciana, Fadilla; Zainil, Melva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematics learning outcomes of fifth-grade students of SD Negeri 33 Sawahan, Padang City on the subject of spatial shapes. This study aims to describe the improvement of mathematics learning outcomes through the application of the Project Based Learning (PjBL) model assisted by Mathigon. This research is a Classroom Action Research (CAR) with a qualitative and quantitative approach implemented in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. The research subjects were 22 fifth-grade students of SD Negeri 33 Sawahan, Padang City. The research data were obtained through observation, tests, and documentation, then analyzed using qualitative and quantitative data analysis techniques. The results of the study indicate that the application of the Project Based Learning model assisted by Mathigon can improve the quality of the learning process and student learning outcomes. The percentage of the quality of learning planning increased from 93.75% in cycle I to 95.83% in cycle II. The implementation of learning in the teacher aspect increased from 82.81% to 93.75%, while in the student aspect it increased from 81.25% to 93.75%, with a very good category. In addition, the average learning outcomes in the knowledge aspect increased from 75.00 in cycle I to 90.45 in cycle II. A total of 20 out of 22 students have achieved the Learning Objective Achievement Criteria (KKTP), so that the research success indicator has been achieved. Thus, the application of the Project Based Learning model assisted by Mathigon is effective in improving mathematics learning outcomes in the material of spatial shapes in class V of SD Negeri 33 Sawahan, Padang City.